Design of Integrated Electrochromic-Photovoltaic Technology for Smart Windows to Improve Building Performance and Energy Efficiency: A Material Approach - Laurentius Kevin Hendinata; Ahmad Ilham Rokhul Fikri; Michael Alfano Suprapto (Indonesian Journal of Energy, 2022)
Energy and climate problems that occur encourage the intensification of energy use efficiency, one of which is in buildings. The building sector is the largest contributor to energy consumption when compared to other sectors due to the need for comfort in life, including to regulate air temperature, ventilation, and artificial lighting. Window innovation as a building component leads to adaptive smart windows technology that has energy saving features. The use of these windows is attractive because they are designed to adapt to changing environmental conditions to minimize large heat losses by adjusting their transmissivity and conductivity. Various types of smart windows have developed, one of which is electrochromic technology as dynamic glass technology which has been widely used as smart windows in commercial buildings. Several studies have shown that its use in buildings has been shown to save energy consumption in buildings through the HVAC and lighting aspects. However, in today's technology, its performance still requires external power to adjust their optical conditions. Therefore, the innovation in developing electrochromic smart windows technology that is integrated with photovoltaic technology is an interesting thing to do. The combination of the electrochromic solution with photovoltaic Si-TFSC placed on a glass substrate provides promising optical performance and energy benefits. The integration of electrochromic and photovoltaic devices provides better efficiency in energy saving, because photovoltaic and electrochromic devices can achieve electrochromic layer discoloration without an external power source. Given the photoelectric and optical modulation properties of electrochromic photovoltaic windows that can function as solar cell modules as well as powered smart windows on their own, this technology has a major advantage in applying sustainable energy to buildings. In its application in buildings, to improve device performance, the control system can be applied by adjusting environmental conditions according to the sensor system readings to obtain better device performance.